Charge manipulation and nitrate displacement on B horizons of an Udox soil - Alcântara, Marco Aurélio Kondracki de; de Camargo, Otávio Antonio (Pesquisa Agropecuaria Brasileira, 2010)
The objective of this work was to evaluate the influence of pH and of the addition of carbonates, phosphates and sulphates on nitrate movement in columns composed by a subsuperficial horizon of an Udox soil. The experiments were carried out according to the miscible displacement technique. A 10 or 40-mmol L-1 KNO3 solution was used as nitrate pulse. Nitrate breaktrough curves were obtained for all columns. The net charge varied from -24.0 to +35.0 mmolc L-1 in the different treatments. In the treatments that received additions of hydrochloric acid, hydrochloric acid + phosphate, carbonate + phosphate and sulphate nitrate, recovery was greater than the total amount applied as pulse. Carbonate, phosphate and sulphate additions favored nitrate leaching, displacing nitrate breaktrough curves to the left. Soil acidification delayed nitrate movement, displacing breaktrough curves to the right. Soil nitrate movement was more influenced by the pH of the environment and by the presence of carbonates, phosphates and sulphates than by the ionic strength of the pulse.